Binary phase-only gallium oxide diffractive optical element for beam shaping - Wei Jia; Steve Blair; Berardi Sensale-Rodriguez (Scientific Reports)
Abstract This study presents an experimentally validated demonstration of an inverse-optimized binary phase-only gallium oxide diffractive optical element (DOE). This DOE transforms an incident Gaussian beam into a square flat-top beam at the working plane. The design methodology for this binary phase-only DOE beam shaper is founded on an efficient process that integrates the modified Gerchberg-Saxton algorithm and the adjoint method. Experimental characterization of the fabricated device on a single crystal $$(\overline{2} \; 01)$$ gallium oxide substrate is conducted at a wavelength of 532 nm, confirming its ability to transform an incident Gaussian beam into a focused square flat-top beam. Such a device holds significant promise for various high-power laser applications, notably in laser welding and similar domains. Furthermore, because of the ultrawide bandgap of gallium oxide, DOEs operating at shorter wavelengths in the UV are also possible based on this technique.